An elusive quest for a region: Darbhanga Raj, caste and language in late colonial India - Chakravartty, Aryendra (The Indian Economic & Social History Review, 2024)
This essay is an exploration of the contingent nature of identity formation in late colonial India. In the wake of the 1912 separation of Bihar and Orissa from Bengal, two distinct conceptions of the region of Mithila and Maithila identity gained prominence. First, the Darbhanga Maharaja viewed Mithila as a bastion of brahmanical orthodoxy, and this underpinned the claims for Mithila to be converted to a native state with its own ruling chief. Second, by the 1930s we see the consolidation of a movement which proposed the Maithili language as the marker of a Maithila people, one that did not make brahmanical orthodoxy or Hinduism a prerequisite to belonging. Both these discourses accepted the mythic conception of Mithila, and its traditional puranic geography, yet the Darbhanga Maharaja embraced all-India markers of belonging by emphasising Hinduism and presenting himself as the leader of brahmanical orthodoxy in India. The local, in this discourse, found validation by embracing national markers, even as the nation itself remained colonised. On the other hand, the Maithili language movement, which gained momentum in the twilight of colonial rule and in post-independence India, emphasised and embraced the local. This essay therefore charts the gradual shift in the conception of Maithila identity where language displaces religion and brahmanical orthodoxy, as championed by the Darbhanga Maharaja, to become the marker of local identity.
Keywords: Colonial History; Darbhanga Raj; Social Hierarchy; Sociolinguistics